The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.radi.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Continuing professional development (CPD) in radiography: A collaborative European meta-ethnography literature review

Abstract: The primary feature of CPD activity should be the resulting impact - to patients, the service, the profession and the individual; with all stakeholders working in partnership. CPD activity must be flexible/multi-modal to support the changing growth/dynamic workforce. All stakeholders should utilise communication and technology resources and make efforts to improve collaboration between the management, regulators and educators to support Radiographers to develop meaningful CPD. Health services across Europe are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 43 publications
4
11
0
1
Order By: Relevance
“…What matters is that such development is characterized as a growing process of awareness and mastery of know-how at work. This is evidenced in different researches that point to reflective practice as an important element for professional development processes [26,27]. Therefore, in addition to promoting training and development events for specific activities, leaders should encourage a critical and reflective vision in their respective work teams with a deliberately planned direction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…What matters is that such development is characterized as a growing process of awareness and mastery of know-how at work. This is evidenced in different researches that point to reflective practice as an important element for professional development processes [26,27]. Therefore, in addition to promoting training and development events for specific activities, leaders should encourage a critical and reflective vision in their respective work teams with a deliberately planned direction.…”
Section: Resultsmentioning
confidence: 99%
“…In this broader view of the professional development process, it stems from formal or informal learning actions [18], being directly related to career progression [11]. Thus, the concept of professional development encompasses a variety of practices, such as: activities in scientific societies [19]; training processes, including acting as supervisor, coach, or leader (mentoring and monitoring of actions to students, subordinates, or new professionals) [20]; training and strategies for systematized and informal learning for skills development [16,21,22]; in-service training [5,23]; participation in communities of practice [24,25]; participation in processes of continuous professional development [5,26]; peer collaboration mediated by technological resources [27,28]; mentoring programs [29]; and specific leadership development programs [10,30].…”
Section: Professional Developmentmentioning
confidence: 99%
“…Findings in this area concur with many studies narrating the benefits of using technology in lifelong learning activities among adults. For instance, Wareing et al (2017) suggested that technology in CPD has the capacity to promote collaborative learning on a hospital inter-department levels and has the potential to provide additional learning spaces in case of practice shift from classroom-based to e-based platforms. Considering that most healthcare providers seem time-lacking in pursuing continuous learning in CPD activities (Ikenwilo and Skåtun 2014), remote learning through asynchronous mode using technology is a promising field.…”
Section: Discussionmentioning
confidence: 99%
“…We found a clear shift away from quantitative, time-serving models towards outcomes-focused ones. (62) in their review of literature relating to radiography, detected that although many countries still use CPD credits/points/hours, there is a move towards the inclusion of outcomes-based elements and a more reflective-based approach.…”
Section: Discussionmentioning
confidence: 99%